1976
DOI: 10.1136/bmj.1.6019.1171
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained hepatitis following halothane.

Abstract: SummaryFull clinical and laboratory details of 203 patients with postoperative jaundice were submitted to a panel of hepatologists. All patients whose jaundice may have had an identifiable cause were excluded, which left 76 patients with unexplained hepatitis following halothane anaesthesia (UHFH). Hepatitis in 95°o of these cases followed multiple exposure to halothane, with repeated exposure within four weeks in 551)O of cases. Twenty-nine patients were obese, 52 were aged 41-70, and 53 were women. Thirteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
6

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(39 citation statements)
references
References 20 publications
1
32
0
6
Order By: Relevance
“…A trifluoroacetyl chloride adduct, which could be the trifluoroacetylated cytochrome P-450, appeared on the rat hepatocyte membrane (19). Moreover, evidence was provided that sera from several patients recovering from severe hepatitis after halothane treatment contained specific anti-organelle autoantibodies, called anti-LKM1 in that case (1,4,20). These antibodies were found to interact specifically with hepatocytes from halothane-treated rabbits and to activate their destruction by lymphocytes (4).…”
Section: Discussionmentioning
confidence: 99%
“…A trifluoroacetyl chloride adduct, which could be the trifluoroacetylated cytochrome P-450, appeared on the rat hepatocyte membrane (19). Moreover, evidence was provided that sera from several patients recovering from severe hepatitis after halothane treatment contained specific anti-organelle autoantibodies, called anti-LKM1 in that case (1,4,20). These antibodies were found to interact specifically with hepatocytes from halothane-treated rabbits and to activate their destruction by lymphocytes (4).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, obese patients could be more prone to develop drug-induced acute hepatitis. This has been suggested for the volatile halogenated anaesthetic halothane [287][288][289], APAP [290,291], and different drugs, such as losartan, ticlopidine, and omeprazole [292]. Interestingly, it has been reported that diabetes also increases the risk of acute liver failure (ALF), including drug-induced ALF [293].…”
Section: Obesity and Type 2 Diabetesmentioning
confidence: 97%
“…However, these factors appear to be associated with specific IDRs [16]. Although women appear to be at increased risk for IDRs caused by some drugs (e.g., halothaneinduced hepatitis) and for idiopathic autoimmune reactions (e.g., lupus and autoimmune thyroid disease), other autoimmune diseases, such as type 1 diabetes, do not have such a female predominance [16,56]. Similarly, while the risk of drug-induced liver toxicity (e.g., isoniazid and acetaminophen) increases with age, the risk of valproic acid liver toxicity is greater in children than adults [16].…”
Section: Characteristics and Mechanisms Of Idiosyncratic Drug Reactionsmentioning
confidence: 99%
“…Similarly, while the risk of drug-induced liver toxicity (e.g., isoniazid and acetaminophen) increases with age, the risk of valproic acid liver toxicity is greater in children than adults [16]. Halothane-induced hepatotoxicity occurs more commonly in obese patients, which is attributed to the distribution of halothane to fat, thereby requiring higher doses of drug to achieve effect [56]. Although it is generally believed that preexisting liver disease does not increase susceptibility to hepatic IDRs, there appears to be exceptions to this dogma [16,57].…”
Section: Characteristics and Mechanisms Of Idiosyncratic Drug Reactionsmentioning
confidence: 99%